Analysis of the Implementation of Hotel Tax Collection on Tour Boats in West Manggarai Regency, East Nusa Tenggara Province Year 2019-2022 - Santoso, Teguh; Nahut, Natalia; Rahmawati, Aninda; Milleano, Dani (Yayasan Sinergi Kawula Muda, 2023)
Tourist who travel to tourist destinations using tourist vessels and utilize accommodation services on board generate transactions that generate revenue. However, the collection of hotel tax on tourist vessels in West Manggarai Regency has not met the target set by the local government. This phenomenon indicates a low level of taxpayer compliance. Therefore, it is essential to implement the Regent Regulation of West Manggarai Regency No. 58 of 2017 regarding the Procedures for Hotel Tax Collection on Tourist Vessels. The objective of this research is to analyze the implementation of the Regent Regulation on the Procedures for Hotel Tax Collection on Tourist Vessels and identify the obstacles faced and efforts made by the Regional Financial Management Agency to overcome these challenges. The research methodology employed in this study is qualitative with a descriptive type. The findings reveal that the implementation process of the Regent Regulation on the Procedures for Hotel Tax Collection on Tourist Vessels has not been executed effectively and doues not comply with the applicable rules due to a lack of education and information dissemination, inadequate human resources capabilities, low implementor supervision, insufficient personnel, and suboptimal inter-organizational communication. Therefore, there is a need to enhance activities related to socialization, education, supervision, and human resources training.